2012
DOI: 10.1124/jpet.112.196832
|View full text |Cite
|
Sign up to set email alerts
|

A TRPC3 Blocker, Ethyl-1-(4-(2,3,3-Trichloroacrylamide)Phenyl)-5-(Trifluoromethyl)-1H-Pyrazole-4-Carboxylate (Pyr3), Prevents Stent-Induced Arterial Remodeling

Abstract: TRPC-mediated Ca 21 entry has been implicated in the control of smooth muscle proliferation and might represent a pivotal mechanism underlying in-stent restenosis. As we have observed significant expression of TRPC3 in human smooth muscle from the coronary artery as well as the aorta, we tested the efficiency of a recently discovered TRPC3 selective Ca 21 entry blocker Pyr3 to prevent vascular smooth muscle proliferation and stent implantation-induced hyperplasia of human aorta. The effect of Pyr3 on prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
(57 reference statements)
1
29
0
Order By: Relevance
“…42 The action site of pyr3 is located on the external side of the TRPC3 protein, and similar acute actions of pyr3 were noted in human coronary artery smooth muscle cells and microvascular endothelial cells. 42,43 DAG analog OAG has been routinely used as a direct activator of receptor operated channels TRPC3 and -6 independently of protein kinases C and without the generation of inositol trisphosphate. 59 Nonselective blockers SKF96365, Gd 3+ , and 2-APB were also used to further validate the implication of TRP channels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…42 The action site of pyr3 is located on the external side of the TRPC3 protein, and similar acute actions of pyr3 were noted in human coronary artery smooth muscle cells and microvascular endothelial cells. 42,43 DAG analog OAG has been routinely used as a direct activator of receptor operated channels TRPC3 and -6 independently of protein kinases C and without the generation of inositol trisphosphate. 59 Nonselective blockers SKF96365, Gd 3+ , and 2-APB were also used to further validate the implication of TRP channels.…”
Section: Discussionmentioning
confidence: 99%
“…This might be because of a positive feed-forward regulation of TRPC3; in fact, this positive feed-forward regulation of TRPC signaling was reported for excessive TRPC activation in other cell types. 43,99 During tissue injuries, such as those occurring in kidney diseases, mesenchymal and inflammatory cells secrete a wide array of profibrotic and inflammatory cytokines, such as TGF-b1, Ang II, and endothelin I, contributing to the differentiation of fibroblasts into myofibroblasts. 71,86 Furthermore, the ERK signaling pathway is activated in UUO and may provide approaches in preventing progression of renal fibrosis.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…28, 32 The idea that TRPCs contribute particularly in inflammatory and remodeling contexts is supported by studies of Trpc gene-disrupted mice and effects of TRPC chemical inhibitor. [33][34][35] One such study has suggested that TRPC3 is a driver of the nuclear translocation of zyxin, 36 an important signal for stretch-induced gene expression. from cells or animals carrying long-term disruption of a gene or several genes encoding TRPCs.…”
Section: Vascular Relevance Of Trpc Channelsmentioning
confidence: 99%